The Impact of Cost Information Type, Gender Differences, and Product Durability on Sustainable New Product Development - Sulistyani, Salsabila Khusnul; Jatiningsih, Dyah Ekaari Sekar (Universitas Muhammadiyah Semarang, 2025)
This study examines the influence of cost information type, gender differences, and product durability on sustainable new product development (S-NPD). This research uses a quantitative experimental method with a 2x2x2 factorial between-subjects design. Participants are active third-semester and fifth-semester students from the Accounting Study Program, Universitas Muhammadiyah Yogyakarta, representing professional designers. They will be given various tasks based on diverse combinations and information. Data is analyzed using the homogeneity test and ANOVA. The research results indicate that product durability significantly impacts S-NPD, in contrast to the type of cost information and gender differences, which do not have a significant impact on S-NPD. Furthermore, this study's findings support the TBL theory, which emphasizes the balance between economic, environmental, and social aspects in S-NPD. This research provides important implications for designers and companies in creating more environmentally friendly products through gender-based and sustainability strategies. However, this research is limited to the participation of students as experimental subjects, so the generalization of the results must be done with caution. Further research should involve professional designers and expand the variables to gain a more comprehensive understanding of S-NPD.